Implementation of Interactive E-Worksheet Building Flat Side Space in Mathematical Problem Solving - Ferdiani, Rosita Dwi; Setia Lestari, Wijayatin Hari; Fayeldi, Trija (Jurnal Pendidikan Matematika IKIP Veteran Semarang, 2025)
This study analyzed mathematical problem-solving ability reviewed from the Honey and Mumford learning style using an Interactive E-Worksheet on Flat-Sided Space Structure material. The learning style used in this study is the Honey and Mumford learning style, which consists of four types: Reflector, pragmatist, theorist, and activist. This descriptive study employs a qualitative approach, incorporating both interview-based and experiment-based research methods. To determine students' learning styles, the researcher provided a questionnaire classified by Honey and Mumford. The subjects of this study were 30 students of class VII A of SMP Negeri 26 Malang. Based on the study results, it is known that subjects with a reflector learning style are less able to understand the steps to solve problem number 1. The subjects of the pragmatic learning style are less able to understand the steps to solve problem number 1 and do not work on problem number 2. The subjects of the theoretical learning style can understand the problem of solving problem number 1, but they still make mistakes, and they do not work on problem number 2. In contrast, the subjects of the activist learning style are less able to understand the steps to solve problem number 1. Thus, research is needed to determine the problem-solving ability of students across different topics and learning media, taking into account their learning styles.